ANALISIS PENENTUAN HARGA POKOK PENJUALAN PADA RUMAH MAKAN MANGATTA EMPANG POMALAA - Amir, Aminah Dina; Chairunnas, Arnadi; Ilham, Surianto (Jurnal Akuntansi Kompetif, 2025)
This research aims to analyze the determination of Cost of Goods Sold (COGS) at Mangatta Empang Pomalaa Restaurant. In a climate of intense business competition, especially among Micro, Small, and Medium Enterprises (MSMEs), the accurate determination of selling prices is a crucial factor for business sustainability and profitability. A common problem faced by business actors is the accuracy of cost calculation underlying product selling price determination. Although a restaurant operationally involves food preparation processes, in the context of this research, Mangatta Empang Restaurant is viewed as a trading entity, focusing on the acquisition and sale of ready-to-serve dishes. Accurate COGS calculation is essential not only as a basis for setting competitive and profitable selling prices but also as a benchmark for operational efficiency and a support for strategic business decision-making. Therefore, this research is expected to provide an in-depth understanding of the COGS calculation methods applied at Mangatta Empang Pomalaa Restaurant and their implications for product selling price determination. Keywords: Cost of Goods Sold; Restaurant; Trading Business; Selling Price.